33. Optical coherence tomography and visual evoked potentials combined use as monitoring tools in Multiple Sclerosis patients. Issue 1 (January 2015) - Guerrieri, S.; Di Maggio, G.; Santangelo, R.; Ferrari, L.; Medaglini, S.; Rodegher, M.; Colombo, B.; Moiola, L.; Del Carro, U.; Martinelli, V.; Comi, G.; Leocani, L.
<x xml:space="preserve">Abstract</x> In Multiple Sclerosis-MS, optical coherence tomography-OCT is used to measure retinal nerve fiber layer-RNFL thickness as a marker of axonal loss and visual evoked potentials-VEPs as an indicator of demyelination. However, no clear indications are available on their combined use in MS monitoring. 80 MS patients underwent neurological and neurophysiological evaluation with OCT and VEPs, with routine clinical and MRI monitoring for a mean period of 1 year. Additional OCT-VEPs follow-up was obtained in 50 patients. Comparing eyes with and without previous ON, VEP latency and RNFL thickness were respectively significantly higher (131.2 ms Vs 118.8 ms, p = 0.008) and lower (78, 15 μm Vs 90, 00 μm, p < 0.001) in the first subgroup. No significant differences were found between the two subgroups when analyzing VEP latency and RNFL thickness evolution during the follow-up period. However, eyes with baseline recent ON had significant reduction in VEP latency (−15, 3 ms) and RNFL thickness (−7, 7 μm) at follow-up. No significant correlation was found between OCT-VEPs parameters and disease activity. Similar results were found when considering only RR and CIS patients. The main role for OCT and VEPs in short-to-medium term follow-up programs would consist in monitoring neural damage after acute ON.